2011
DOI: 10.1007/s00330-011-2086-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery stenosis: comparative assessment by unenhanced renal artery mra versus contrast-enhanced MRA

Abstract: Our study has shown Unenhanced-MRA to be a viable alternative to CE-MRA, yielding images equal in quality without the requirement for gadolinium contrast agents. The sensitivity and specificity for the detection of haemodynamically significant stenoses are comparable to CE-MRA. Potentially, Unenhanced-MRA could be used as an initial investigation to avoid performing CE-MRA in patients with normal renal arteries, however we suggest that its real value will lie in being complementary to CE-MRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…From the analysis of our series and also from the literature, NC-MRA has proved to be superior to CE-MRA in identifying intraparenchymal arterial branches (22,24,28) due to the high signal to noise ratio that characterizes the SSFP sequence (9). Also Xu et al reported a better visualization of intraparenchymal branches in comparison with CTA (26); however, if the renal artery trunk is affected by a severe stenosis, the consequent signal loss downstream the stenosis can lead to poor visualization of peripheral branches (26,27).…”
Section: Discussionmentioning
confidence: 95%
“…From the analysis of our series and also from the literature, NC-MRA has proved to be superior to CE-MRA in identifying intraparenchymal arterial branches (22,24,28) due to the high signal to noise ratio that characterizes the SSFP sequence (9). Also Xu et al reported a better visualization of intraparenchymal branches in comparison with CTA (26); however, if the renal artery trunk is affected by a severe stenosis, the consequent signal loss downstream the stenosis can lead to poor visualization of peripheral branches (26,27).…”
Section: Discussionmentioning
confidence: 95%
“…[678] The NC MRA technique of ASL with 3D SSFP sequence has been evaluated in some recent studies to assess renal vascular anatomy and has produced promising results. [2122] In the current study, we compared Inhance Inflow IR Renal MRA, basically ASL with 3D SSFP sequence and CTA in preoperative renal donors evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The SSFP technique was used because the previous studies demonstrated that in addition to a high SNR, this sequence bears intrinsically high (T2-like) contrast between the blood pool and soft tissue. [141516171819202122] SSFP imaging is supposed to be flow compensated in all three spatial coordinates due to the symmetric shape of the gradient pulses. [1823] The application of an SS inversion prepulse as used in this study resulted in a good signal suppression of static tissue and veins, which allowed the selective visualization of the renal arteries without the use of any contrast medium application.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic Resonance Angiography (MRA) is a noninvasive imaging modality that has been widely used for stenosis detection and screening [1,3].…”
Section: Introductionmentioning
confidence: 99%